Paparan Polusi Udara dalam Ruangan dan Risiko Penyakit Paru Obstruktif Kronik (PPOK): Tinjauan Sistematis - Intan Nabilla; Disa Hijratul Muharramah; Novida Syafitri; Aulia Putri Zean; Cass Marcella Rasnino; Sefriliza Zenia; Ika Dwi Puspa; Nadya Tri Melda; Nadya Indah Khoirunnisa (KOLONI, 2026)
This study aimed to analyze the association between exposure to indoor air pollution and the incidence of Chronic Obstructive Pulmonary Disease (COPD) based on a synthesis of epidemiological studies. A systematic review was conducted on cohort, cross-sectional, and case-control studies evaluating exposure to biomass fuels, indoor air pollution, and individual factors associated with COPD incidence. Literature searches were performed in PubMed, ScienceDirect, Springer Nature, and DOAJ, yielding 1,863 records in the initial stage. After screening, duplicate removal, and eligibility assessment based on inclusion and exclusion criteria, 10 studies were included in the final analysis. The findings showed that most studies reported a significant association between indoor air pollution exposure and an increased risk of COPD, with OR values >2 in several studies. Biomass fuels such as firewood, charcoal, coal, crop residues, and animal dung were associated with higher COPD risk, while PM2.5 concentrations and poor household ventilation further amplified the effects of exposure. Women were also found to have a higher risk than men. In conclusion, indoor air pollution is an important risk factor for COPD development, influenced by fuel type, exposure intensity, and individual and environmental factors. Prevention efforts through the use of clean fuels, improved ventilation, and increased public awareness are necessary to reduce the burden of COPD.